Calculation of power losses in a frequency inverter - Al-Rawashdeh, Ayman Y.; Dunayev, Mikhail Pavlovich; Alzyoud, Khalaf Y.; Dovudov, Sarfaroz U. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This study's main goal is to make a new simulation model of the power losses calculation block for frequency converter power switches that can correctly figure out the transistors and diodes' static and dynamic power losses in a 1.5 kW SIEMENS SINAMICS G110 semiconductor converter (SSG110SC). We use simulation modeling tools in the MATLAB/Simulink environment to look at the semiconductor circuits of a rectifier and an autonomous pulse-width modulation voltage inverter. The study presents analytical expressions describing static and dynamic power losses in power semiconductor diodes and transistors. We used polynomials to get close to the power characteristics of insulated-gate bipolar transistor or IGBTs and then used mathematical expressions to show how they depend on Erec (Ic), Vse (Ic), Vf (If), Eon (Ic), and Eoff (Ic). By utilizing the acquired expressions, a MATLAB/Simulink block was constructed to calculate static and dynamic power losses. as well as power loss dependences on switching frequency and load current, were computed utilizing the developable block system. By comparing the simulation outcomes of the present study to the data provided by the manufacturer, the results were validated. Specific diode and transistor characteristics can be accounted for by the method developed in the present study.